2016
DOI: 10.21608/jalexu.2016.188586
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Glomus Intraradices (AMF) and Different Isolates of PGPR (Biotol) to Enhance the Yield and Quality of Wheat Grown in The Field in Calcareous Soil Under Different Salinity Levels

Abstract: Two field experiments were carried out at the farm of Nubaria Agricultural Research Station during the two winter seasons of 2012/2013 and 2013/2014, to study the effect of the arbuscular mycorrhizal fungus, Glomus intraradices and the plant growth promoting rhizobacteria (Biotol) on growth, yield parameters and chemical contents of two wheat cultivars (Sakha 93 and Gemmeza 9) grown in calcareous soil under four levels of soil salinity and four rates of NPK mineral fertilizers. Results indicated that, wheat pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…AMF promote the reduction in Na + and Cl − ions uptake, contributing to maintaining vacuolar membrane stability and facilitating the sequestration of Na + into plants’ vacuoles. This mechanism has been reported in several cereal crops, including wheat [ 58 , 59 ], maize [ 56 , 60 , 61 , 62 ], rice [ 63 , 64 , 65 ], and sorghum [ 63 , 66 , 67 ]. Selvakumar et al [ 61 ] found higher K + /Na + and ZmAKT2 (a phloem-expressing K + channel), ZmSOS1 (with ability to extrude Na + and control xylem loading for a long-distance Na + transport), and ZmSKOR (involved in the translocation of K + towards shoots through xylem) gene expression in maize root inoculated with Gigaspora margarita or Claroideoglomus lamellosum .…”
Section: Building Resilience: Harnessing Mycorrhizal Symbiosis For En...mentioning
confidence: 81%
“…AMF promote the reduction in Na + and Cl − ions uptake, contributing to maintaining vacuolar membrane stability and facilitating the sequestration of Na + into plants’ vacuoles. This mechanism has been reported in several cereal crops, including wheat [ 58 , 59 ], maize [ 56 , 60 , 61 , 62 ], rice [ 63 , 64 , 65 ], and sorghum [ 63 , 66 , 67 ]. Selvakumar et al [ 61 ] found higher K + /Na + and ZmAKT2 (a phloem-expressing K + channel), ZmSOS1 (with ability to extrude Na + and control xylem loading for a long-distance Na + transport), and ZmSKOR (involved in the translocation of K + towards shoots through xylem) gene expression in maize root inoculated with Gigaspora margarita or Claroideoglomus lamellosum .…”
Section: Building Resilience: Harnessing Mycorrhizal Symbiosis For En...mentioning
confidence: 81%